Impact of computer expertise, locus of control and self-esteem on computer-induced stress (2004)
The present study considered the influence of self-esteem, locus of control and computer expertise on computer-induced stress in a cross sectional survey. One hundred and fifty cyber cafe users drawn from. 10 cyber cafes randomly chosen from University of Ibadan and its environs participated in the study. Of the 150 respondents, 27 (31.3%)were females while 103 (68.7%) were males; mean age was 25.41 with a standard deviation of 7. 00. Result indicated that the main effect of self-esteem was significant, F {1, 142)=6.32, P<.05. Computer expertise also had a significant effect on computer-induced stress F (I, 142) =28. 04, P<. 001. As hypothesized, high self-esteem persons reported lower level of computer induced stress than low self-esteem persons. Also, people with higher level of computer expertise reported lower computer-induced stress than people with less computer expertise. The implication and results were discussed and suggestions for further studies were highlighted in the light of the findings.